Secondary polycythemia causing renal artery thrombosis and presenting with acute abdominal pain – A case report - Goutham, K; Ramkumar, G; Sadhwani, Neha (Indian Journal of Case Reports, 2024)
AbstractWe present the case of a 52-year-old gentleman presented with acute abdominal pain. He has a personal history of 20 pack year smoking and his hematocrit was 62.8%. With subsequent investigations, a diagnosis of renal artery thrombosis due to smoker’s polycythemia was made. The patient symptomatically improved with hematocrit reduction after the phlebotomy. Renal artery thrombosis due to smoker’s polycythemia is a rare entity and needs a high index of suspicion for prompt diagnosis and treatment. This case report reviews the causes of polycythemia, it’s differentials, pathophysiology, and management.